Framing microfinance in Australia – gender neutral or gender blind?. Issue 2 (June 2013) - Goodwin, Susan; Voola, Archana Preeti
Abstract : In Australia, microfinance is gaining visibility as a distinct poverty alleviation strategy. Within the Australian microfinance policy and program discourses, the microfinance sector is framed as targeting both men and women equally. Yet at the practice level, the majority of loan recipients are women. Such a gender neutral framing is in stark contrast to microfinance policy and practices developed elsewhere. This paper explores how gender is represented in microfinance policy and practice in Australia, drawing on an analysis of the policy and practice statements of Australian microfinance programs. It is argued that the robust feminist assessments of the relationship between microfinance and gender equality that have emerged in developing countries could usefully inform Australian developments in this area of social policy, but that this shift requires acknowledging gender in the framing of the problem Australian microfinance seeks to address.